2003
DOI: 10.1213/01.ane.0000069507.93582.6e
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Safety and Efficacy of Administering Rofecoxib for Postoperative Pain Management

Abstract: In children undergoing tonsillectomy, a single preoperative dose of rofecoxib decreases 2- and 24-h pain and decreases nausea and vomiting at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 29 publications
1
47
0
4
Order By: Relevance
“…Children completed measures of pain, depression (CDI), and use of coping strategies (KidCope), and the primary caregiver completed the Brief Symptom Inventory (from which the depression subscale was used for the present study). Results of discriminant function analyses conducted separately for younger children (ages 7-12) and adolescents (13)(14)(15)(16)(17)(18) found that only the coping and caregiver depression variables significantly contributed to distinguishing clinical levels of depression in this sample. However, results varied by age: for younger children, caregiver depression was significantly more influential in distinguishing children who were versus who were not clinically depressed than child coping strategies.…”
Section: E32 Distinguishing Clinical Levels Of Depression In Childrenmentioning
confidence: 80%
See 1 more Smart Citation
“…Children completed measures of pain, depression (CDI), and use of coping strategies (KidCope), and the primary caregiver completed the Brief Symptom Inventory (from which the depression subscale was used for the present study). Results of discriminant function analyses conducted separately for younger children (ages 7-12) and adolescents (13)(14)(15)(16)(17)(18) found that only the coping and caregiver depression variables significantly contributed to distinguishing clinical levels of depression in this sample. However, results varied by age: for younger children, caregiver depression was significantly more influential in distinguishing children who were versus who were not clinically depressed than child coping strategies.…”
Section: E32 Distinguishing Clinical Levels Of Depression In Childrenmentioning
confidence: 80%
“…In this study we investigated whether youth with disabilities could successfully use the NRS and we examined the relationships among different types of pain intensity ratings. 112 participants, aged [8][9][10][11][12][13][14][15][16][17][18][19][20]SD=1.24), were asked to use an 11-point NRS to rate their current pain, least, worst, and average pain over the past week. There were no significant differences by sex or disability in any of the four pain intensity ratings.…”
Section: G11 Measuring Pain In Youth With Disabilitiesmentioning
confidence: 99%
“…Celecoxib was as effective as naproxen in children with juvenile rheumatoid arthritis (Foeldvari et al, 2008 Level II). Small-scale efficacy studies evaluated different perioperative doses of rofecoxib (prior to its withdrawal from the market): low dose (0.625 mg/kg) was inferior to ibuprofen (in combination with paracetamol) (Pickering et al, 2002 Level II); 1 mg/kg was superior to placebo (Joshi et al, 2003 …”
Section: Coxibsmentioning
confidence: 99%
“…Anhand der Daten wurde errechnet, dass für 30-60 operierte Patienten eine zusätzliche Operation notwendig wird. Die Schlussfolgerungen der Autoren beider Metaanalysen waren nicht einheitlich: In einer Arbeit wurde zur Vorsicht geraten [106], in der anderen wurden von jeglichem -auch postoperativen -Einsatz von NSAID bei Tonsillektomien abgeraten [103].Bisher wurde in einer Studie der intraoperative Blutverlust bei Tonsillektomien nach Gabe von COX-2-Inhibitoren untersucht und kein erhöhter Verlust festgestellt [75].Nach derzeitigem Wissen ist es unwahrscheinlich, dass COX-2-Inhibitoren das Risiko für blutungsbedingte Reoperationen erhöhen -allerdings liegen hierzu bisher keine Daten vor.…”
Section: Darstellung Und Bewertung Der Studienlageunclassified